Egalitarianism in the Process of Modern Economic Growth : The Case of Sweden - Andersson, Martin (Washington, DC: World Bank, 2012)
An analytical framework is developed to study the long-term relationship between equality and growth. The authors demonstrate the interconnectedness by studying the process of structural change in Sweden during the last two centuries, emphasizing the country's drive to Modern Economic Growth. The Swedish case demonstrates that agricultural transformation, paved the way for surplus production and commercialization. This was because egalitarianism, both in terms of equality of opportunity and in terms of institutionalizing individual rights, played a central role in Sweden. The authors argue that while the successful Swedish development obviously is unique and conditioned by specific historical circumstances, valuable lessons can be drawn for current LDCs.